Living with Lynching - lvalue lvalue (Universitat Jaume I. Department of English Studies, 2019)
Reviewed by M. Mar Gallego Durán University of Huelva, Spain   The volume authored by Koritha Mitchell is a remarkable contribution to the field of African American drama, as it explores the manifold uses of lynching plays during the Progressive era as crucial tools to ensure community conversation and debate about the difficulties and complexities involved in having to coexist with the terrible reality of lynching. [...]